Two Loci, RiAF3 and RiAF4, Contribute to the Annual-Fruiting Trait in Rubus - Jibran, Rubina; Spencer, Jessica; Fernandez, Gina; Monfort, Amparo; Mnejja, Mourad; Dzierzon, Helge; Tahir, Jibran; Davies, Kevin; Chagné, David; Foster, Toshi M. (Frontiers in Plant Science, 2019)
Most Rubus species have a biennial cycle of flowering and fruiting with an intervening period of winter dormancy, in common with many perennial fruit crops. Annual-Fruiting varieties of raspberry (R. idaeus and R. occidentalis L.) and blackberry (R. subgenus Rubus) are able to flower and fruit in one growing season, without the intervening dormant period normally required in Biennial-Fruiting (BF) varieties. We used a red raspberry (R. idaeus) population segregating for AF obtained from a cross between NC493 and ‘Chilliwack’ to identify genetic factors controlling AF. Genotyping by sequencing was used to generate saturated linkage maps in both parents. Trait mapping in this population indicated that AF is controlled by two newly identified loci (RiAF3 and RiAF4) located on Rubus linkage groups (LGs) 3 and 4. The location of these loci was analyzed using single nucleotide polymorphism (SNPs) markers on independent red raspberry and blackberry populations segregating for the AF trait. This confirmed that AF in Rubus is regulated by loci on LG 3 and 4, in addition to a previously reported locus on LG 7. Comparative RNAseq analysis at the time of floral bud differentiation in an AF and a BF variety revealed candidate genes potentially regulating the trait.